2004
DOI: 10.2188/jea.14.s12
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Mortality in Japan: The Miyagi Cohort Study

Abstract: Cigarette smoking is an established risk factor for all-cause mortality among Caucasians 1-8 as well as Japanese. [9][10][11] Since smoking habit often accompanies with unhealthy lifestyle, appropriate control for confounding factors is necessary to estimate the hazard of cigarette smoking.12-14 However, there have been only one Japanese study that analyzed the relative risk (RR) for all-cause mortality associated with cigarette smoking adjusted for possible confounders.9 Therefore, we conducted a prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
25
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 16 publications
(15 reference statements)
14
25
1
Order By: Relevance
“…The six-prefecture cohort study 29 The Miyagi Cohort Study 31 The Japan Public Health Center-based Prospective Study 30 The Jichi Medical School Cohort Study 33 were higher than those of the present study. Other reports showed that the RRs of current smokers were higher than our results.…”
Section: Japancontrasting
confidence: 60%
See 1 more Smart Citation
“…The six-prefecture cohort study 29 The Miyagi Cohort Study 31 The Japan Public Health Center-based Prospective Study 30 The Jichi Medical School Cohort Study 33 were higher than those of the present study. Other reports showed that the RRs of current smokers were higher than our results.…”
Section: Japancontrasting
confidence: 60%
“…30 The Miyagi Cohort Study (MCS) followed up 36,052 subjects aged 40-64 years during an 11-year period, 31 and the multivariate-adjusted RRs were 1.71 in males and 1.44 in females. The results of these two studies for males approximated ours and a comparison was reasonable because their research was similar to ours in terms of subjects, observation time, and period of observation.…”
mentioning
confidence: 99%
“…Significant gender differences observed in smoking status and the quartile of FVC %pred in this survey are typical with respect to differences that have been reported repeatedly by numerous researchers, both in Japan and overseas (2,(34)(35)(36).…”
Section: Discussionsupporting
confidence: 73%
“…This finding provided support for smoking habits as a significantly independent predictor of higher mortality. Several studies have presented the same relationship between smoking habits and mortality (6,(33)(34)(35)(36). It has been reported, in a Japanese population, that smoking habits significantly increase the risk of premature death among middle-aged Japanese men and women, and that a substantial proportion of deaths, especially in men, is attributable to smoking (34).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation